The Duration of Consonants in a Stressed Syllable: Its Relation to Logical Stress - Tankevičiūtė, Marytė (Kalbotyra, 1982)
Basing on a number of instrumental studies, it has been round that every particular group of Lithuanian consonants may be characterized by its individual duration. Both in unstressed and stressed syllables the consonant duration depends on the same factors. The present experiment deals with the interdependence of consonant duration and the place of logical stress. It has been found that the duration of consonants in stressed syllables is greatly dependent on the logical stress, being quite independent on it in unstressed ones. Thus, the duration of consonants may be considered a constant value revealing some deviations in pre-stress and post-stress positions in a phrase. The decrease of the consonant duration by about 17% in the above-mentioned positions may be considered an important key to the absence of logical stress.